2014
DOI: 10.1093/ecco-jcc/jju011
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery in Patients with Inflammatory Bowel Disease: An Accessible Path? Report of a Case Series and Review of the Literature

Abstract: Bariatric surgery seems to be safe and effective in IBD patients. Concomitant ileocolic resection does not increase perioperative complications. Relationship between IBD and obesity remains unclear, but weight loss could be useful in the pharmacological control of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Although bariatric surgery is technically feasible in patients with IBD, long-term consequences of major restrictive and malabsorptive procedures in these individuals are poorly understood. Case series have suggested that these procedures are safe in highly selected patients who are morbidly obese and have IBD, and have also anecdotally observed improvement in disease activity after weight loss 115,116 . However, short of bariatric surgery, other weight loss interventions would also probably be beneficial.…”
Section: Obesity Treatment and Ibd Outcomesmentioning
confidence: 99%
“…Although bariatric surgery is technically feasible in patients with IBD, long-term consequences of major restrictive and malabsorptive procedures in these individuals are poorly understood. Case series have suggested that these procedures are safe in highly selected patients who are morbidly obese and have IBD, and have also anecdotally observed improvement in disease activity after weight loss 115,116 . However, short of bariatric surgery, other weight loss interventions would also probably be beneficial.…”
Section: Obesity Treatment and Ibd Outcomesmentioning
confidence: 99%
“…Morbid obesity is also an emerging problem in the IBD population . Sleeve gastrectomy has previously been reported to have the dual benefit of weight loss and IBD remission .…”
mentioning
confidence: 99%
“…Nijhuis et al [36] found a significant decrease in serum calprotectin levels (in 11 out of 15 patients) from a mean of 119.6 ± 31.5 ng/ml to a mean of 93.9 ± 42.7 ng/ml (p < 0.001) 2 years postoperatively, suggesting a state of lower neutrophil activation following BS-induced weight loss. Theoretically, the decreased inflammatory state following BS might favorably impact the evolution of IBD; however, surgically induced malabsorption and abdominal surgery including intestinal manipulation might also adversely impact IBD patients [37,38,39]. The eventual complications that may be more frequent in IBD include anastomotic leak, fistula, abscess, bowel stricture, and bowel obstruction [40].…”
Section: Outcomes Of Bs In Ibd Patientsmentioning
confidence: 99%
“…Furthermore, 3 patients were able to stop their 5-ASA treatment. Colombo et al [38] reported successful BS procedures in 6 IBD patients with concomitant or deferred IBD surgery: SG in 5 CD and 1 UC and vertical banded gastroplasty in 1 CD patient. The authors observed only one perioperative complication (reoperation for staple line bleeding), effective BMI reduction, and absence of intestinal malabsorption.…”
Section: Outcomes Of Bs In Ibd Patientsmentioning
confidence: 99%
See 1 more Smart Citation